Application Of Reward And Punishment In Increasing Maharatul Kalam At Darussalam Islamic Boarding School In Garut - Tsamrotul Fuadah, Wafa; Egi, Egi; Karim Fatkhullah, Faiz (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
The application of reward and punishment is one of the strategies that are suitable to be applied in language learning, because it has a great impact on improving the ability to speak foreign languages. This study aims to describe and describe the application of rewards and punishments at Darussalam Garut Islamic Boarding School. This research is presented with a qualitative approach with a descriptive method. Data collection was conducted through interviews, observations, and documentation studies. Data processing is done using interactive analysis or data reduction. The results of this study show that the application of reward and punishment can improve the ability of maharatul kalam santri. This success is supported by activities such as muhadhoroh, Arabic storytelling and muhadatsah which are carried out regularly.